Incidence of neurocutaneous melanosis in Japanese pediatric patients with congenital melanocytic nevi - Miyuki Takiya; Yasutaka Fushimi; Michiharu Sakamoto; Takeshi Yoshida; Kentaro Ueno; Satoshi Nakajima; Akihiko Sakata; Sachi Okuchi; Sayo Otani; Hiroshi Tagawa; Naoki Morimoto; Yuji Nakamoto (Scientific Reports, 2023)
Abstract Neurocutaneous melanosis (NCM) is a rare, non-hereditary neurocutaneous disorder characterized by excessive melanocytic proliferation in the skin and central nervous system. As no major studies have covered the incidence of NCM among Japanese patients with congenital melanocytic nevi (CMN), we prospectively investigated the incidence of NCM among Japanese patients who underwent initial treatment for CMN. The relationship of CMN and NCM was also investigated. Japanese pediatric patients with CMN under 1 year of age were included between January 2020 and November 2022, and all patients underwent brain MRI to check for NCM in this study. NCM lesions were most frequently seen in the amygdala, followed by the cerebellum, brainstem, and cerebral hemispheres. NCM was diagnosed on brain MRI in 31.6% of the 38 patients with CMN and in 25.0% of patients with no prior examination or treatment. Distribution and size of CMN, number of satellite nevi, rugosity and nodules were strongly associated with the existence of NCM, and these findings may guide a future registry study with a large cohort of CMN patients.